Effects of temperature and loading rate on the mechanical properties of a high temperature epoxy adhesive - Banea, M. D.
The variation of the mechanical properties of adhesives with temperature and strain rate is one of the most important factors to consider when designing a bonded joint due to the polymeric nature of adhesives. It is well known that adhesive strength generally shows temperature dependence. Moreover, in many structural applications, the applied loads can be dynamic and the design of the joint requires the knowledge of the high loading rate mechanical behaviour of the adhesive. In this study, the combined effect of the temperature and test speed on the tensile properties of a high temperature epoxy adhesive was investigated. Tensile tests were performed at three different test speeds and various temperatures (room temperature (RT) and high temperatures (100, 125 and 150◦C)). The glass transition temperature (Tg) of the epoxy adhesive investigated is approximately 155◦C. The ultimate tensile stress decreased linearly with temperature (T) while increased logarithmically with the loading rate, which is in the accord with the Airing’s molecular activation model.